Challenges of Law Enforcement Against International Network-Based Human Trafficking in Indonesia - Daliuwa, Nadia Putri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study analyzes the challenges of law enforcement against international human trafficking networks in Indonesia, which have become increasingly complex due to digital technology developments, cross-border jurisdictional differences, and limitations in national institutional capacity. Using a normative-juridical and empirical approach, the research finds that international syndicates exploit socio economic vulnerabilities, regulatory gaps, and weak interagency coordination to carry out the recruitment, transfer, and exploitation of victims. The main obstacles identified include difficulties in cross jurisdictional evidence gathering, the absence of an integrated national database, limited digital forensic capabilities, and inadequate victim protection, all of which hinder investigative processes. Moreover, international cooperation mechanisms have not functioned optimally due to slow information exchange and differing evidentiary standards. This study emphasizes the need to strengthen legal instruments, enhance technical capacity, modernize investigative technology, and harmonize cross-border cooperation to improve the effectiveness of Indonesia’s efforts in combating international human trafficking networks.